Does oxygen exposure time control the extent of organic matter decomposition in peatlands?. Issue 5 (27th May 2014) - Philben, Michael; Kaiser, Karl; Benner, Ronald
Abstract The extent of peat decomposition was investigated in four cores collected along a latitudinal gradient from 56°N to 66°N in the West Siberian Lowland. The acid:aldehyde ratios of lignin phenols were significantly higher in the two northern cores compared with the two southern cores, indicating peats at the northern sites were more highly decomposed. Yields of hydroxyproline, an amino acid found in plant structural glycoproteins, were also significantly higher in northern cores compared with southern cores. Hydroxyproline‐rich glycoproteins are not synthesized by microbes and are generally less reactive than bulk plant carbon, so elevated yields indicated that northern cores were more extensively decomposed than the southern cores. The southern cores experienced warmer temperatures, but were less decomposed, indicating that temperature was not the primary control of peat decomposition. The plant community oscillated between Sphagnum and vascular plant dominance in the southern cores, but vegetation type did not appear to affect the extent of decomposition. Oxygen exposure time appeared to be the strongest control of the extent of peat decomposition. The northern cores had lower accumulation rates and drier conditions, so these peats were exposed to oxic conditions for a longer time before burial in the catotelm, where anoxic conditions prevail and rates of decomposition are generally lower by an order of magnitude.